2000
DOI: 10.2486/indhealth.38.224
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Heavy Metals on Transcription Factor Sp1.

Abstract: Heavy metals are expected to affect the biological activity of various metal-containing proteins, including transcriptional regulators. We studied the effects of several heavy metal ions on the DNA-binding activity of a Zn-finger transcription factor, Sp1. With respect to both DNA elements through which Sp1 acts positively and negatively, Cd . These results suggest that the toxic potential of heavy metals could be largely influenced by the intracellular Zn 2+ concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Reaction mixtures were incubated at 25°C for 20 min and analyzed by native 5% polyacrylamide gel electrophoresis and autoradiography as described previously (16,37). A double-stranded oligonucleotide containing the sequence 5Ј-TTTTCTGCTGAGTCAAGGTCCG-3Ј was used as a probe in EMSA reactions (core StRE sequence is underlined).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction mixtures were incubated at 25°C for 20 min and analyzed by native 5% polyacrylamide gel electrophoresis and autoradiography as described previously (16,37). A double-stranded oligonucleotide containing the sequence 5Ј-TTTTCTGCTGAGTCAAGGTCCG-3Ј was used as a probe in EMSA reactions (core StRE sequence is underlined).…”
Section: Methodsmentioning
confidence: 99%
“…IRPTCs were seeded (1 ϫ 10 6 cells/10-cm plate) and cultured for 48-72 h in complete medium and then treated with vehicle or 10 M heme in serum-free medium for 3 h. Whole cell extracts (WCEs) were prepared as described previously (16). The standard binding reaction mixture (12.5 l) contained 18 mM HEPES (pH 7.9), 80 mM KCl, 2 mM MgCl 2, 10 mM DTT, 10% glycerol, 0.2 mg/ml bovine serum albumin, 160 g/ml poly(dIdC), 20,000 counts per minute [␥-…”
Section: Methodsmentioning
confidence: 99%
“…Reaction mixtures were incubated at 25°C for 20 min and analyzed by native 5% polyacrylamide gel electrophoresis and autoradiography as described previously (29,30). A double-stranded oligonucleotide containing the sequence 5Ј-GATCTTTTATGCTGAGTCATGGTTT-3Ј (core StRE underlined) was end-labeled by T4 polynucleotide kinase, purified on a 10% polyacrylamide gel, and used as probe in EMSA reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Interactions of these nonspecific complexes with molecular oxygen leads to the formation of reactive oxygen species such as H 2 O 2 , resulting in oxidative stress within the cell (23). In addition to oxidative stress, complexation of sulfhydryl groups with heavy metal cations results in reduced activity of sensitive enzymes (16). Previous studies identified several examples in which heavy metals were toxic to cellular processes, including the following.…”
mentioning
confidence: 99%